The Rates of Cement Leakage Following Vertebroplasty in Osteoporotic versus Metastatic Disease - Saad, Ahmed; Botchu, Rajesh; James, Steven (Indian Journal of Radiology and Imaging, 2022)
Introduction Percutaneous vertebroplasty is used for symptomatic osteoporotic fractures and osteolytic neoplasms. We performed a retrospective study to analyze the pattern of leaks in the two cohorts.Material and Methods Vertebroplasties performed over a 7-year period at a tertiary orthopaedic center were included in the study and divided into osteoporotic and neoplastic groups. The incidence and pattern of cement leaks in each group were documented and analyzed.Results There were 75 leaks of a cohort of 211 vertebroplasties with a relatively equal proportion in osteoporotic and neoplastic groups. The incidence of discal leaks was comparable between the two groups. Lateral and posterior leaks were more common in the neoplastic group.Conclusion We report the incidence and type of leaks in osteoporotic and neoplastic groups. Understanding the fracture pattern and preoperative management are both essential in preventing cement leakage. Using highly viscous cement or allowing the cement to harden prior to injection, with use of low pressure, decreases the risk and incidence of cement leakage.
Keywords: vertebroplasty; osteoporotic; neoplastic; leak